Vi sono ragioni della libertà note al cuore e all’intelletto: il triplo sguardo sulla libertà espresso nei Ritiri spirituali di Parigi di Józef Tischner - The Person and the Challenges Volume 6 (2016) Number 1, p. 55–66 DOI: http://dx.doi.org/10.15633/pch.1657 Inga Mizdrak (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
In its analysis of human freedom, Józef Tischner’s philosophy poses fundamental questions about the essence of freedom, but also about the sense of preservation of freedom in one’s life. Freedom appears as a primary phenomenon, something that is part and parcel of human nature. Freedom as a structural element of human existence manifests itself perhaps most clearly in the sphere of human relations, which, immersed as they are in the eternal drama of good and evil, are played out in the space between salvation and damnation. The binary character of values, best seen in our use of freedom, keeps us for ever mindful of that unavoidable drama a man has to face, owing to his freedom, need not be helpless. Using such categories as election, space and health of the soul in his Rekolekcje Paryskie, Tischner approaches the definition of freedom through a succession of essential modifications which articulate some fundamental points concerning relations between people and man’s relations with God from an anthropological, axiological, ethical, social and theological perspective. Tischner proposes no definitive interpretation of freedom but, viewing the controversy over freedom as one of the most difficult problems in the philosophy of man, he tries to show what man’s inner freedom consists in and what achievements it makes man capable of.